Application of Discovery-Inquiry Learning Strategy in Tajweed Learning to Improve Al-Qur'an Reading Skills for High School Students: Penerapan Strategi Discovery-Inquiry Learning pada Pembelajaran Ilmu Tajwid dalam Meningkatkan Kemampuan Baca Al-Qur’an Siswa Sekolah Menengah Atas - Santoso, Rachmad Putro; Salahuddin, Rahmad (Indonesian Journal of Education Methods Development, 2022)
This study intends to provide treatment using the Discovery-Inquiri Learning learning strategy as an effort to innovate and improve the scope of recitation learning at Senopati Sedati Senior High School to improve the students' reading ability, especially in class X. This study uses Classroom Action Research (CAR) techniques. conducted in two cycles, namely Cycle I and Cycle II. The results of this study indicate that: (1) The implementation of the Discovery-Inquiry Learning Strategy is carried out in 6 stages, namely stimulation, problem identification, data collection, data processing, verification, and generalization. (2) The learning strategy of Discovery-Inquiri Learning is able to improve the ability to read the Qur'an of class X students of SMA Senopati Sedati by increasing the ability to read the Qur'an of students in the pre-cycle, the average score is 63.6 with a mastery percentage of 41%, experienced an increase in the first cycle with an average value of 74.2 with a percentage of completeness of 69%, and in the second cycle the average value reached 83.5 with a percentage of completeness of 90%.